Reading Romans 6:1-4 To A New Life - Putrawan, Bobby Kurnia; Daryanto, Daryanto (Universitas Islam Negeri Raden Intan Lampung, 2022)
Sin is the main obstacle to God’s salvation, because the wages of sin is death. But salvation is God’s free gift, not because of the kindness of those who receive it to God. Baptism was used by Paul to explain the death of sin and life for God. Believers are baptized into Christ, are baptized in His death, which means believers are drowned in Christ, into the death of Him. And by the resurrection of Christ, those who die in Christ will also experience a resurrection with Christ. From this resurection with Christ, this is the faithful person who has a new life and starts walking in that new life. This article attempts to explain Paul's words in Romans 6: 1-4 about new life. And it is in this new life that believers have a quality life knowing God who is new and full of wisdom. And a new life here is a very different life from a long life, where a long life tands to sin, but a life that tends to be old is a wise life.